4CPS-028 Statin overuse? Evaluation of statin initiation for primary prevention during hospitalisation between two neighbouring countries in europe in high-risk patients. (March 2019) - Haider, D; Arthofer, B; Drofenik, P; Gržinič, N; Haider, C; Petre, M; Pointinger, A; Ravnikar, M; Schneider, I; Tomšič, T
Abstract : Background: Due to Guidelines of the ESC/EAS the number of patients recommended to receive statin therapy for primary prevention of atherosclerotic cardiovascular disease (ASCVD) has increased. Critical voices expressed concern that implementation of these guidelines may lead to statin overuse. ESC/EAS recommend using risk calculators for Systematic COronary Risk E valuation (SCORE) to estimate patients' 10 year fatal ASCVD risk. However, data identifying statin utilisation based on SCORE in European hospitals is lacking. Purpose: The aim of the study was to evaluate whether there is a difference in the treatment of patients with high risk between two neighbouring countries in Europe according to ESC/EAS guidelines. Material and methods: A multi-site, international, retrospective, cross-sectional study was conducted in three hospitals in Austria and three hospitals in Slovenia. At each site approximately 20% monthly discharges from selected wards were reviewed. For each patient data on age, gender, lipid levels, smoking status, systolic blood pressure, serum creatinine, liver function, presence of cardiovascular disease (CVD) or diabetes and prescribed cholesterol lowering agents was collected. Ten-year risk for fatal CVD was calculated using SCORE low-risk charts. Patients with SCORE calculation ≥5 and patients with diabetes were classified as high risk. Results: We included 138 Austrian patients (mean age 61.9±10.3; 52.2% men) and 198 Slovenian patients (mean age 63.4±10.6; 57.6% men). Patients from Slovenia were at higher risk compared to patients from Austria (64.1% versus 49.3%; p=0.07). 77.1% of high-risk patients from Austria and 56.3% from Slovenia did not receive a statin during hospitalisation (p=0.009). In 16.7% of Austrian and 58.1% of Slovenian patients, LDL was measured during the hospital stay. 7.1% of high-risk Austrian patients with no statin had LDL <2.6 mmol/L compared with 8.5% of high-risk Slovenian patients. Conclusion: In the population we investigated that there is no risk of statin overuse so far. Despite robust evidence of their efficacy and safety, statin use is still low in high-risk patients in primary prevention for ASCVD in both countries according to ESC/EAS guidelines. Clinical pharmacists could play an important role in improving the use of statins and thus reducing preventable CVD morbidity and mortality. References and/or acknowledgements: Current guidelines on prevention with a focus on dyslipidaemia. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5418212/ No conflict of interest.